The Role Of Professional Supervision In Child Protection Services In Malaysia: A Direction Towards Best Practice - Chan, Soak Fong (2019)
Supervision is an important component of all areas of professional social work practice, particularly in high risk areas where clients are at risk of or are being harmed. Supervision of staff is of particular importance in child protection practice. The benefits of supervision to agencies, professional practitioners and clients, and the contribution of good supervision to best practice in child protection is widely recognised. The purpose of the study is to identify how respondents understand supervision within a professional practice environment and how this understanding may then act to shape the expectations of what supervision should be in the future. This is an exploratory qualitative study, based on 23 in-depth interviews with present and past practicing workers in the statutory child protection system or associated with the statutory system. The study findings highlight supervision is an important and crucially needed component of the provision of professional child protection services within the statutory agency in Malaysia. The provision of best practice supervision is significantly related to facilitating competent statutory child protection practice.